Pelaksanaan Perlindungan Hukum Kontrak Kerja Tenaga Kesehatan di Lingkungan Dinas Kesehatan Kota Palembang - Desrina, Desrina; Emirzon, Joni; Suatmiati, Sri; Mahfuz, Abdul Latif (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The purpose of this paper explains the increase in honorary or contract personnel to support the performance of civil servants, especially in the context of public services in local governments. Public services are closely related to the community, and contract labor plays an important role in realizing maximum service. The focus of this research is on the implementation of employment contracts and legal protection for health workers at the Palembang City Health Office. This research uses normative research methods with a focus on regulations and written legal materials. Data collection techniques are carried out through documentation, involving data collection through documents related to research problems. The document includes primary, secondary, and tertiary legal materials. Data analysis is carried out in depth and comprehensively with an analytical descriptive approach to answer problems in research. The analysis is carried out by considering the variation of data and the basic nature of the data that is not easily quantified, as well as thorough and holistic. The results showed that the work implementation agreement at the Padang Tuesday Health Center was a form of a certain time work agreement, with valid regulations and conditions based on Article 1320 of the Civil Code. However, the laws and regulations on which the legal basis for the appointment of contract workers do not specifically address the legal rights and protections for contract workers, indicating that there are loopholes that must be addressed.